Cortical folding and the potential for prognostic neuroimaging in schizophrenia. (November 2015) - Guo, Shuixia; Iwabuchi, Sarina; Balain, Vijender; Feng, Jianfeng; Liddle, Peter; Palaniyappan, Lena
Summary: In 41 patients with schizophrenia, we used neuroanatomical information derived from structural imaging to identify patients with more severe illness, characterised by high symptom burden, low processing speed, high degree of illness persistence and lower social and occupational functional capacity. Cortical folding, but not thickness or volume, showed a high discriminatory ability in correctly identifying patients with more severe illness.